The Malaysian Political Economy: Economic Transformation & the Expansion of Islamic Economics - Abdalrahman Mohamed Migdad; Harun Adams Babangida Babangida (Faculty of Economics and Management, 2022)
This paper aims to shed light on Malaysian economic development in light of demographics and politics while focusing on economic legislation that had the largest effect on the outlook of the nation known to the world today. Then the paper discusses the beginnings of how Islamic economics was introduced to the scene and how the industry developed wider and faster than most Islamic economies in the world. This paper also explains this rapid development in the context of the nation’s political-economic development. The paper is qualitative and analytical; it addresses developments up to 2017 although few discussions extend beyond that period, for many developments after 2017 were not significant enough to change the perspectives. The paper incorporates fieldwork, observations, and interviews that took place in 2017. The paper concludes that certain socio-economic policies need to be updated to suit today's generations and allow for the continuation of development at high rates. Furthermore, the expansion of Islamic economics is beneficial; however, the industry demands detail and procession more than ever, especially in sharia compliance, This matter is important because it associates to customer trust that is highly significant for continues development in the industry.